2015
DOI: 10.1371/journal.pone.0144599
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of Thyroid-Stimulation Blocking Antibody Prevents High Bone Turnover in Untreated Premenopausal Patients with Graves’ Disease

Abstract: Osteoporosis-related fractures are one of the complications of Graves’ disease. This study hypothesized that the different actions of thyroid-stimulating hormone receptor (TSHR) antibodies, both stimulating and blocking activities in Graves’ disease patients might oppositely impact bone turnover. Newly diagnosed premenopausal Graves’ disease patients were enrolled (n = 93) and divided into two groups: patients with TSHR antibodies with thyroid-stimulating activity (stimulating activity group, n = 83) and patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 34 publications
0
4
1
Order By: Relevance
“…Before treatment the GD patients who had osteoporosis in our study were characterized by being significantly older, being a greater number of years after menopause, having a significantly lower BMI, and having significantly higher serum total ALP, serum BAP, and serum NTX levels than the normal BMD group. Some studies have reported finding an inverse correlation between BMD and TRAb titers [8,16,18,19], but another study reported finding a positive correlation between BMD and TRAb titers [20]. The results of our study showed a negative correlation between TRAb titers and BMD in the DR, but the correlation coefficient was low.…”
Section: Discussioncontrasting
confidence: 68%
“…Before treatment the GD patients who had osteoporosis in our study were characterized by being significantly older, being a greater number of years after menopause, having a significantly lower BMI, and having significantly higher serum total ALP, serum BAP, and serum NTX levels than the normal BMD group. Some studies have reported finding an inverse correlation between BMD and TRAb titers [8,16,18,19], but another study reported finding a positive correlation between BMD and TRAb titers [20]. The results of our study showed a negative correlation between TRAb titers and BMD in the DR, but the correlation coefficient was low.…”
Section: Discussioncontrasting
confidence: 68%
“…According to some studies, antiTSH-R may have negative impact on bone metabolism ( 38 , 39 ). Other studies have shown that antiTSH-R could have a protective effect on bone ( 40 ). Possible explanations involve thyroid status, i.e.…”
Section: Clinical Relevance Of Thyrotoxicosis For Bmd and Fracture Riskmentioning
confidence: 99%
“…Different results were reported regarding the impact of antiTSH-R on bone metabolism, ranging from having a protective role on bone tissue to stimulation of bone loss ( 25 , 40 , 70 ). This effect could depend on the status of thyroid hormones and whether euthyroidism, subclinical or over hyperthyroidism is present.…”
Section: Possible Pathophysiological Mechanism Involved In the Revers...mentioning
confidence: 99%
“…show an increase in procollagen type I N-terminal propeptide (PINP), a marker of bone formation, validating the conclusion that a bolus dose of TSH is indeed anabolic in people (Martini, et al 2008). Likewise, antibody-activated TSH signaling contributes to high bone formation, independent of the actions of thyroid hormone (Cho, et al 2015).…”
Section: Tsh and Bone Mass Regulationmentioning
confidence: 99%